The debates and disagreements on human sexuality and the Anglican Church of Southern Africa : a theological assessment with special reference to the prophetic witness of Archbishop Tutu - Maluleke, Tinyiko S. (University of Pretoria, 2024)
Dissertation (MTh (Science of Religion and Missiology))--University of Pretoria, 2023.